Overview of Peruvian women in STEM careers - Rabines Floreano, Madeleine Gillian (2024)
This article provides an overview of the participation of Peruvian women in various STEM (science, technology, engineering, and mathematics) careers at licensed universities in Peru. It presents an analysis of data collected from the Ministry of Education (Minedu) and the General Directorate of University Higher Education (Digesu) for the period 2017-2022, focusing on the participation of women and men in different STEM careers across the regions of Peru. Including women in these careers represents a challenge that begins at the school level, where the aim is to promote digital learning as a tool that allows girls and adolescents to explore disciplines related to science, technology, engineering, and mathematics practically, thus empowering them to decide to pursue a university career related to STEM in the future. The analysis shows a progressive increase in the participation of women in STEM careers between 2017 and 2022, which is certainly encouraging.